Plasma metabolomic profiles reveal sex- and maturation-dependent metabolic strategies in sea lamprey (Petromyzon marinus) - Tamrakar, Sonam; Huerta, Belinda; Chung-Davidson, Yu-Wen; Li, Weiming (Metabolomics: Official Journal of the Metabolomic Society, 2022)
INTRODUCTION: Adult sea lamprey (Petromyzon marinus) cease feeding and migrate to spawning streams where males build nests, undergo final sexual maturation, and subsequently produce and release large quantities of bile acid pheromones that attract mature females. These animals are predicted to rearrange their metabolic pathways drastically to support their reproductive strategies, presenting advantageous opportunities to examine how sex and the maturation processes affect metabolism. OBJECTIVES: The objective is to investigate the metabolic differences between sexes and maturation states in sea lamprey that support changes in physiological functions. METHODS: We compared plasma metabolomes of spawning and prespawning sea lamprey in both sexes using both non-targeted and targeted metabolomics approaches using UPLC/MS-MS with electrospray ionization in both positive and negative modes. The data were processed using Progenesis QI, Compound Discoverer and XCMS softwares for alignment, peak picking, and deconvolution of the peaks. Principle component analyses (PCA) and partial least squares discriminant analyses (PLS-DA) were performed using SIMCA and Metaboanalyst softwares to identify discriminating features, followed by fragmentation matching with extensive database search and pathway mapping. RESULTS: The pheromonal bile acid biosynthesis was upregulated significantly in males compared to females. Spermiating males further upregulated bile acid biosynthesis by altering amino acid metabolisms, upregulating cofactors and nucleotide metabolisms, but downregulating carbohydrate and energy metabolisms. CONCLUSION: Plasma metabolomes are sex- and maturation-dependent and reflect the special metabolic demands at each life stage and reproductive strategy.
Keywords: Animals; Bile Acids and Salts; Bile acid biosynthesis; Female; Male; Metabolic pathways; Metabolomics; Petromyzon; Petromyzon marinus; Sexual Maturation; Sexual selection; Tandem Mass Spectrometry; Targeted analyses; Untargeted analyses; dept.che; peer-reviewed